(untitled) (Nepal Journal of Neuroscience, 2026)
Background: Epilepsy is a complex neurological condition in which cognitive impairments in unstable patients are extensively documented. there is a lack of research concerning cognitive outcomes in patients who are clinically stable while on medication. Objectives: This study aimed to delineate the cognitive profile of stable epilepsy patients and examine the relationship between cognitive domains and clinical variables such as seizure frequency, illness duration, and age. Methods: A cross-sectional study was conducted at Burdwan Medical College (January–December 2017) involving 50 epilepsy patients stable on medication for at least three months. Cognitive function was assessed using the Post Graduate Institute Battery of Brain Dysfunction (PGI-BBD). Statistical analysis utilized Pearson correlation to identify associations between clinical factors and cognitive domains. Results: Despite clinical stability, significant cognitive variations were observed. Remote memory demonstrated a constant, highly significant negative correlation with seizure frequency (r = -0.360, p = 0.010), illness duration (r = -0.511, p = 0.000), and age (r = -0.465, p = 0.001). Conversely, visual retention and attention/concentration showed significant positive correlations with illness duration and age, suggesting potential compensatory neural mechanisms. Other domains, including performance quotient, remained relatively stable. Conclusion: Clinical stability in epilepsy with anti-epileptic’s drugs or without does not avert the gradual decline of remote memory function. These observations indicate a "cognitive fingerprint" reflecting selective susceptibility in long-term memory, even when attentional skills remain intact. Upcoming therapeutic approaches should include cognitive rehabilitation and ongoing assessment to maintain long-term quality of life.